Evaluation of nicotine dependence and attitudes towards public spot advertisements in medical school students - Baha, Ayşe; Ogan, Nalan; Akpınar, Evrim Eylem (Journal of Dependence, 2018)
Objective: The purpose of this study is to investigate the frequency of smoking among medical faculty students and attitudes towards public spot advertisements (PSA).Method: Students in our medical faculties were questioned about their attitudes towards PSAs about cigarette and tobacco use by the survey method.Results: Of the 314 students, 194(61.8%) were female and 120(38.2%) were male. 12(%12,9) of the smokers believed that PSAs support to quit smoking. Students who did not smoke thought that PSAs were an important factor in smoking cessation, also these students thought PSAs are good to express damage of cigarette. Students who quit smoking thuought that the smoking cessation effect of PSAs weaker. Also, these students were more negative than the others about the PSAs are good to express damage of cigarette. The rate of discomfort from PSAs about of cigarettes was higher those who quit smoking.Conclusion: While the point of view of the PSAs towards the benefits and quality is the most positive among the ones who have never used the cigarette, it is the most unfavorable among those who have left the cigarette.
Keywords: medical students; addict of cigarette; public spot ads